LEGAL PROTECTION OF CONTRACT OBJECT COVERAGE CLAIMS AT TAKAFUL INSURANCE COMPANY, Ltd.: A REVIEW OF DECISION NO.0177/Pdt.G/2016/MS Bna - Al-fitra, Ahmad Farhan (JURISTA: Jurnal Hukum dan Keadilan, 2024)
This article aims to find out how the protection of Takaful Insurance participants against claims filed by client in the enet of loss of the contract object (car) according to sharia economic law. The research methode used is qualitative in the form of content analysis ont the Decision of the Judge of the Banda Aceh Sharia Court. Based on the result of the research, that in the case of a lawsuit filed by the plaintiff against PT Asuransi Takaful Banda Aceh, the panel of judges rejected the plaintiff’s claim. The judge argued that the parties had not followed the procedures contained in the insurance policy. Because the panel of judges did not find the fact of peace and deliberation between the plaintiff and defendant within 60 days. In the case, the judge did not determine the decision in accordance with the plaintiff’s claim because the settlement of the case between the parties could be resolved amicably in accordance with the policy clause.